HAZRATI IMOM (HASTIMOM) ME’MORIY MAJMUASINIG QAYTA TIKLANISHI - Usarov Jamoliddin Tolkinovich (Western European Studies, 2024)
As you know, every architecture has been used, restored, repaired, restored and sometimes restored according to each service. In 2007, the Islamic Organization for Education, Science and Culture - ISESCO (ISESCO) welcomed the announcement of Tashkent as the "Capital of Islamic Culture".
Keywords: His Majesty; cultural; heritage; restoration